HAP1 interacts with 14–3-3 to regulate epileptic seizure via GABAAR-mediated inhibitory synaptic transmission in pentylenetetrazole rat model. (September 2022) - Wen, Yuetao; Zhang, Guangliang; Liu, Lin; Zhang, Peng; lin, Lan; Mei, Rong; Zhang, Fengli; Chen, Yangmei; Li, Rong
Abstract: Disruption of γ-aminobutyric acid type A receptors (GABAA Rs) synaptic clustering and a decrease number in the plasma membrane are thought to contribute to the alteration in the balance between excitatory and inhibitory neurotransmission in the epilepsy. Thus, it is important to elucidate the molecular mechanisms that regulate the stabilities of surface GABAA Rs populations as well as their concentrations at inhibitory synapses. However, the mechanism that delivers GABAA Rs to plasma membrane has not been conclusively determined. Our previous research indicated that huntingtin-associated protein 1 (HAP1), a major facilitator of pathological variations in membrane trafficking, modulates epileptic seizure by regulating GABAA Rs-mediated inhibitory synaptic transmission in pentylenetetrazole (PTZ)-induced epileptic rats. However, a detailed molecular interaction networks comprising GABAA Rs and HAP1 is necessary for studying and investigating new treatment targets for epilepsy. In this study, we indicate that HAP1 specifically interacts with 14–3–3, a protein that functions as a chaperone, forming a cargo adaptor complex to regulate surface GABAA Rs expression and the inhibitory post-synaptic current amplitudes. Disrupting the HAP1/14–3–3 complex decreases the strength of GABAARs-mediated inhibitory synaptic transmission in epilepsy. Taken together, HAP1/14–3–3 complex is linked to inhibitory synaptic transmission in evoking seizures, therefore, it is a possible drug target for epilepsy. Highlights: HAP1 specifically interact with 14–3-3. HAP1/14–3-3 complex inhibits epileptic seizure. 14–3-3/HAP1 is down-regulated in TLE patients and in epileptic rats. HAP1/14–3-3 complex regulate surface GABAA Rs expression and the inhibitory post-synaptic current amplitudes.